PERFORMANCE OF GRAZING NDAMA SUPPLEMENTED WITH OIL PALM SLURRY BASED DIETS (2011)
Ndama, an indigenous cattle to tropical environment, is characterized by slow growth and poor milk production due to inadequate all year round dietary energy supplementation. Oil Palm Slurry (OPS) is an industrial waste that has potential to replace the conventional energy supplements in ruminant diet. However, information on its use as energy supplement is very scanty, particularly for Ndama. Thus, the performance of grazing Ndama cattle supplemented with OPS-based diets was investigated. In the first study, eighteen Ndama in-cows were randomly divided into six groups of three animals per treatment in a completely randomized design such that OPS replaced Wheat Offal (WO) at 0%, 25%, 50%, 75%, 100% and grazing alone (control) in treatments I, II, III, IV, V, and VI respectively for ten months. Parameters measured were Voluntary Feed Intake Supplement (VFIS), Calf Weight at Birth (CWB), Calf Daily Weight Gain (CDWG), Milk Off-take (MO) and Calf Weaning Weight (CWW). In another study, sixteen weaned calves were randomly divided into four groups of four animals per group and fed Panicum maximum supplemented with 0%, 10%, 20% and 30% OPS replacing WO in treatments I, II, III, and IV respectively for 180 days. Parameters measured were VFIS, Total Dry Matter Intake (TDMI), Weight Gain (WG) and Efficiency of Feed Utilization (EFU). The animals were slaughtered to obtain information on carcass qualities such as Dressing Percentage (DP), Meat Color (MC), Shear Force (SF), and Meat to Bone Ratio (MBR). Data obtained were analysed using descriptive statistics and ANOVA (p=0.05). The VFIS (2.46 2.70kg DM/cow/day) and MO (2.54 2.67kg/cow/day) were similar for cows on treatments I-III, but significantly higher than those on treatments IV-VI (1.35 1.53kg DM/ cow/day and 1.37 1.42kg/cow/day respectively). The CDWG and CWW were similar for animals on treatments I-III (0.44 0.50kg and 95.80 97.57kg respectively), but significantly higher than corresponding values obtained for treatments IV-VI (0.22-0.31kg) and (70.17-71.03kg). The VFIS and TDMI were similar for weaners on treatments I, II, and III (1.96 2.04kg and 2.56 2.57kg respectively), but significantly higher than those on treatment IV (1.31 and 2.17kg). The WG (kg/calf/day) for weaners on treatment I (0.48) was significantly lower than those on treatments II (0.58) and III (0.63), but similar to those on treatment IV (0.50). The EFU of weaners on treatments II, III and IV (0.23 - 0.24) were similar but higher than those on treatment I (0.20). The DP (%) of weaners on treatments I (40.86) and IV (43.45) were similar and significantly lower than those on treatments II (49.19) and III (50.99). The MC and SF for weaners on treatments II, III and IV (6.00 7.00% and 5.03 - 5.27% respectively) were similar but significantly higher than those on treatment I (4.00 and 4.23% respectively). The MBR (0.08 0.18) increased significantly from treatment I to III after which it decreased to 0.10. Oil palm slurry can replace up to 50% wheat offal in the diets of Ndama cows while 20% replacement of wheat offal with oil palm slurry in weaner diets enhanced performance and carcass qualities.